Novel insight into the mechanism underlying light-controlled anthocyanin accumulation in eggplant (Solanum melongena L.). (August 2016) - Jiang, Mingmin; Ren, Li; Lian, Hongli; Liu, Yang; Chen, Huoying
Highlights: We functionally characterize SmCRY1, SmCRY2, SmCOP1 and SmHY5 from eggplant. SmCRY1 and SmCRY2 interact with SmCOP1 in a blue-light-dependent manner. SmCOP1 interacts with SmHY5 and SmMYB1. SmHY5 and SmMYB1 both bind the promoters of SmCHS and SmDFR . We provide a new working model underlying light-controlled anthocyanin accumulation. Abstract: Eggplant is rich in anthocyanins, which are the major secondary metabolites and beneficial to human health. We discovered that the anthocyanin biosynthesis of eggplant cultivar 'Lanshan Hexian' was regulated by light. In this study, we isolated two blue light receptor genes, SmCRY1 and SmCRY2, and negative/positive anthocyanin regulatory factors SmCOP1 and SmHY5 from eggplant. In terms of transcript levels, SmCRY1, SmCRY2 and SmHY5 were up-regulated by light, while SmCOP1 was down-regulated. Subsequently, the four genes were functionally complemented in phenotype of corresponding mutants, indicating that they act as counterparts of Arabidopsis genes. Yeast two-hybrid and bimolecular fluorescence complementation assays showed that SmCRY1 and SmCRY2 interact with SmCOP1 in a blue-light-dependent manner. It also obtained the result that SmCOP1 interacts with SmHY5 and SmMYB1. Furthermore, using yeast one-hybrid assay, we found that SmHY5 and SmMYB1 both bind the promoters of anthocyanin biosynthesis structural genes ( SmCHS and SmDFR ). Taken together, blue-light-triggered CRY1/CRY2-COP1 interaction creates the condition that HY5 and MYB1 combine with the downstream anthocyanin synthesis genes ( CHS and DFR ) in eggplant. Our finding provides a new working model by which light controls anthocyanin accumulation in eggplant.